Exploring the Online Students’ Support during the Covid 19 Pandemic towards the Development of the 21st Century Life Skills of LSPU Students - Hermosa, Jherwin P.; Castillo, Albert B. (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
The study sought to determine the extent of the online student support and the 21st century life skills development of the students. Descriptive and correlational study was employed using a self –made questionnaire with 60 respondents. Pearson correlation analysis was used to know the relationship of the two variables. It was found out that the online support in term of student engagement, learning support and mental health are highly practiced. While the 21st century life skills in terms of leadership, responsibility, and teamwork are highly developed. This study is a first step to understand the online support in building of their 21st century life and skills. It may serve as a basis for each institution to review their existing strategies on online support. Sustainable institutionalized faculty program in the support of their students no matter the modality they might employ should be promoted. Further research about the student services and 21st century life and skills could be explore considering the possible balanced portfolio of online and face to face support align to the current status of the pandemic using other variables, more wider respondents and qualitative method to validate or contradict the result.